Let $V$ and $W$ be finite-dimensional vector spaces over some arbitrary field $K$, and let $V^\ast$ and $W^\ast$ be their respective dual spaces. Let $f:V \rightarrow W$ be a linear map.

a) Define the dual of $f$ as the map $f^\ast : W^\ast \rightarrow V^\ast$, $e \mapsto e \circ f$.

b) Suppose we define two fixed non-degenerate bilinear forms $\langle \cdot,\cdot \rangle_V : V^2 \rightarrow K$, $\langle \cdot,\cdot \rangle_W : W^2 \rightarrow K$. Define the adjoint of $f$ as the map $\bar{f}: W \rightarrow V$ satisfying $\langle v,\bar{f}(w) \rangle_V = \langle f(v),w \rangle_W$.

Since the bilinear forms are non-degenerate, the linear maps $\phi_V : V \rightarrow V^\ast$ and $\phi_W : W \rightarrow W^\ast$ given by $$ \phi_V(v)(v_0) = \langle v,v_0 \rangle_V, \qquad \phi_W(w)(w_0) = \langle w,w_0 \rangle_W $$ are isomorphisms. Given this, how can we express $\bar{f}$ explicitly in terms of $f^\ast$ (and if required, $\phi_V$ and $\phi_W$)? Alternatively, how can we prove that the map $\bar{f}$ is guaranteed to exist?

EDIT: As pointed out by @levap I have fixed the definition of $\phi_W$.


For some reason, your definition of the map $\phi_W$ is mangled (the $w$ is missing). Let me fix a convention. Given a vector space $U$, and a bilinear form $\left< \cdot, \cdot \right>_U$ on $U$, define the map $\phi^{R}_U \colon U \rightarrow U^{*}$ by the formula

$$ \phi^{R}_U(u_0)(u) = \left< u, u_0 \right>_U $$

(the letter $R$ is there to designate that we use $u_0$ as the "rightmost" argument in $\left< \cdot, \cdot \right>_U$). Another meaningful choice would be to define

$$ \phi^{L}_U(u_0)(u) = \left< u_0, u \right>_U $$

(so we use $u_0$ in the left slot instead of the right slot). Unless the bilinear form is symmetric, the maps will be different.

Your definition of the adjoint is the map $\overline{f}$ which satisfies

$$ \left< v, \bar{f}(w) \right>_{V} = \left< f(v), w \right>_W. $$

To express this adjoint, it is better to work with the maps $\phi^R$ and then you have $\overline{f} = \left( \phi_V^R \right)^{-1} \circ f^{*} \circ \phi_W^R$. To see why, note that

$$ \phi_{V}^R(v_0) = \varphi \iff \left< v, v_0 \right>_V = \varphi(v) \,\,\, \forall v \in V $$

where $v_0 \in V, \varphi \in V^{*}$ (one direction is clear from the definition and the other follows because $\varphi_V$ is an isomorphism). Now, fix $v \in V, w \in W$ and then using the above we have

$$ \left< v, \left( \phi_{V}^R \right) ^{-1}(f^{*}(\phi_W^R(w))) \right>_V = f^{*}(\phi_W^R(w))(v) = \phi_W^R(w)(f(v)) = \left< f(v), w \right>_W.$$

You could have defined an adjoint of $f$ as the map which satisfies

$$ \left< \bar{f}(w), v \right>_V = \left< w, f(v) \right>_W $$

instead and in general, this would give you a different adjoint which is given by $\left( \phi_V^{L} \right)^{-1} \circ f^{*} \circ \phi_W^L$.

In fact, there are two other reasonable definitions of the adjoint in this general context and each of them can be expressed in terms of $\phi_V^{L},\phi_V^{R},\phi_W^L,\phi_W^{R},f^{*}$. When both $\left< \cdot, \cdot \right>_{V}, \left< \cdot, \cdot \right>_{W}$ are symmetric, all the adjoints coincide.

  • $\begingroup$ It looks like you are using $\phi_V(v)(v') = \langle v',v\rangle_V$ instead of $\phi_V(v)(v') = \langle v, v'\rangle_V$ as given by OP. $\endgroup$ – Christoph Feb 20 '18 at 13:48
  • $\begingroup$ @Christoph: Arg, you are right. The problem is that the definition of $\phi_V, \phi_W$ of the OP is not consistent (the roles of $v_0,v$ and $w_0,w$ are switched which doesn't make any sense as $V,W$ are arbitrary vector spaces so why choose to use one convention for one and another convention for the other). I'll edit my answer. $\endgroup$ – levap Feb 20 '18 at 13:51
  • $\begingroup$ I think it is consistent and just missing a "$(w)$" in "$\phi_W(w)(w_0)$", no? $\endgroup$ – Christoph Feb 20 '18 at 13:59
  • $\begingroup$ @Christoph: Well, it depends whether the OP meant to write $\phi_W(w)(w_0)$ or $\phi_W(w_0)(w)$. In any case, I've edited the answer to treat both conventions. $\endgroup$ – levap Feb 20 '18 at 14:21
  • $\begingroup$ @Christoph Indeed, I meant $\phi_W(w)(w_0)$. Thanks for pointing it out; I have corrected the definition. $\endgroup$ – EpsilonDelta Feb 21 '18 at 4:53

Here's an approach using matrices.

By a choice of basis identify $V=K^n$ and $W=K^m$, elements are column vectors. We can identify their duals $V^*$ and $W^*$ with spaces of row vectors so that the usual matrix product serves as application of linear forms to vectors. In this setting, when $f\colon V\to W$ is given by an $m\times n$-matrix $A$ such that $f(v) = Av$, its dual $f^*\colon W^*\to V^*$ is given by $f^*(\beta) = \beta A$ since then $$ (f^*(\beta))(v) = \beta A v = \beta(f(v)). $$ Your bilinear forms are given by square matrices, namely $$ \langle v, v'\rangle_V = v^t X v' \qquad\text{and}\qquad \langle w, w'\rangle_W = w^t Y w'. $$ for invertible matrices $X_{ij}=(\langle e_i, e_j\rangle_V)_{i,j=1,\dots,n}$ and $Y_{ij}=(\langle e_i, e_j\rangle_W)_{i,j=1,\dots,m}$.

Your isomorphisms $\phi_V \colon V\to V^*$ and $\phi_W\colon W\to W^*$ are given by $\phi_V(v)(v') = v^t X v'$ and $\phi_W(w)(w') = w^t Y w'$.

Now let's find the $n\times m$-matrix $B$ describing the adjoint $\bar f\colon W\to V$ as $\bar f(w) = Bw$. We want to have $$ \langle v, \bar f(w) \rangle_V = \langle f(v), w\rangle_W, $$ which can be written as $$ v^t X B w = (Av)^t Y w = v^t A^t Y w. $$ So we have $XB=A^t Y$ and hence $B = X^{-1} A^t Y$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.